ANALISIS EKONOMI ISLAM PADA SISTEM AKAD PINJAM MEMINJAM DI KOPERASI SIMPAN PINJAM BERINGIN INDRALAYA - Pairan, Fitri; Ayudha Ningsih, Lita (Al-Iqtishad: Jurnal Ekonomi Syariah, 2022)
Contract role important in activity cooperative save borrow. With existence contract activity Becomes more clear, directed, and detailed so that no emergence misunderstanding and no harmful second party later. Destination study this is for knowing how system implementation activity borrow borrow from cooperatives save borrow banyan Indralaya and for knowing how system implementation activity borrow borrow from cooperatives Save Borrow banyan Indralaya according to perspective Islamic economics . Method research used is study qualitative, with type study field research or study field and characteristic descriptive. As for use method data collection through observation, interview, and documentation as well as type primary data sources and secondary . Results study obtained that (1) In the ongoing process contract in the cooperative save borrow banyan Indralaya there is pillars, conditions, mechanisms and form contract that alone. Get along contract in the cooperative this that is existence second split involved parties in agreement, agreement accept, agreement written, object agreement and purpose (2) System contract save loans in cooperatives save borrow banyan Indralaya by whole has Fulfill principles sharia, that is has in line in accordance with pillars, terms, objects, and form contracts that apply in Islamic teachings. And the contracts that happened by whole allowed in Islam. However in activity return loan there is agreement at the beginning that requires pay flower permanent on loan. So that Thing the including in usury qardh and Thing the no Fulfill principle sharia .